CRIMINAL LIABILITY OF PERPETRATORS OF THE CRIME OF THEFT WITH VIOLENCE - Aldy Kurniawan Dika; Sudarto (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
The crime of theft with violence is a crime committed with the aim of facilitating theft, escaping when caught red-handed, or maintaining stolen goods. This crime is regulated in Article 365 paragraph (1) of the Criminal Code which states that theft preceded, accompanied, or followed by violence or threat of violence against persons, shall be punished by a maximum imprisonment of nine years. This research uses normative juridical methods to examine the regulation and criminal liability of perpetrators of theft with violence in Indonesia. Based on judicial practice, one example is found in Tangerang District Court Decision Number 1502/Pid.B/2021/PN.Tng, which imposed a one-year prison sentence on the defendant Andi Firdaus alias Ndi Bin Ardana, because he was legally proven to have committed theft with violence. This decision raises questions regarding the severity of the sentence imposed and the protection of victims. Therefore, it is necessary to reform the national criminal law by regulating more stringent and severe sanctions against perpetrators of theft with violence, either through the new Criminal Code, Government Regulation, or Minister of Law and Human Rights Regulation. In addition to imposing heavy penalties, the state is also expected to provide maximum protection for victims, including compensation for losses and physical and psychological recovery for victims of crime. Thus, the law can be enforced fairly and create order and security in society.